Prognostic analysis of m6A-related genes as potential biomarkers in idiopathic pulmonary fibrosis - Wang, Zhiqiang; Shen, Lanyu; Wang, Junjie; Huang, Jiaqian; Tao, Huimin; Zhou, Xiumin (Frontiers in Genetics, 2022)
Idiopathic pulmonary fibrosis (IPF) is a progressive, fatal lung disease with limited treatment options. N6-methyladenosine (m6A) is a reversible RNA modification and has been implicated in various biological processes. However, there are few studies on m6A in IPF. This project mainly explores the prognostic value of m6A-related genes as potential biomarkers in IPF, in order to establish a set of accurate prognostic prediction model. In this study, we used GSE28042 dataset in GEO database to screen out 218 m6A-related candidate genes with high IPF correlation and high differential expression through differentially expressed gene analysis, WGCNA and m6A correlation analysis. The genes associated with the prognosis of IPF were screened out by univariate Cox regression analysis, LASSO analysis, and multivariate Cox regression analysis, and the multivariate Cox model of prognostic risk of related genes was constructed, riskscore = (-0.44084*RBM11) + (0.631579*RBM47) + (-0.01935*RIC3) + (-0.58291*TRAF5) + (-0.00528*ZNF14). Finally, the prognostic prediction ability and independent prognostic characteristics of the risk model were evaluated by survival analysis and independent prognostic analysis, and verified by the GSE93606 dataset, which proved that the prognostic risk model we constructed has a strong and stable prediction efficiency.